Editorial - Corella Parajeles, Juan Pablo (2016)
Libraries magazine is pleased to present the Vol 34, No. 1, corresponding to January-June 2016. This edition collects four articles on different thematic areas. Innovation in library services and information, evaluation of accessibility of information, methodological for infomediaries evaluation portals and a study on future collaboration among teachers and librarians.